Amalan pengajaran guru di Pondok Bantan, Nakhon Si Thammarat, Thailand - Haziyah Hussin,; Mohd Aderi Che Noh,; Muhamad Razak Idris,; Farid Mat Zain,; Hamdi Ishak,; Salamiah Ab. Ghani,; Abdulroya Panaemalae, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Historically, Pondok Bantan is a traditional Islamic educational institution that applies teacher-centered approach in teaching and learning programmes based on religious texts. However, in line with the changes in needs and time of society, the Pondok is now adopting Thai national curriculum which at the same time integrate with religious education curriculum based on the traditional (turath) texts of Malay scholars. The diversity in its educational curriculum components perceived as a strength for Pondok Bantan but becomes a challenge to the teachers’ ability to implement and ensure the teaching curriculum adopted is efficient for the holistic development of the students. Therefore, this study aims to identify attitudes and approaches applied by Pondok Bantan teachers’ in their teaching activities and the level of teaching aids application. The study applies quantitative research method involving 43 respondents among the teachers of Pondok Bantan. Data are obtained from the questionnaires and then analyzed using the descriptive statistics tehnique to measure the frequency, ranges, mean and standard deviation. The findings show that the teachers’ attitudes and practices toward teaching activities are high either before of the classrooms. However, the use of teaching aids need to be improved in the future by the teachers and the management of Pondok Bantan since its practices are in between moderate and high level.